A Comparative Study between Phase Disposition PWM(PDPWM) and Phase Opposition Disposition (PODPWM) for Cascade H-Bridge, Flying Capacitor and Neutral Point Clamped Multilevel Voltage Source Inverters (MVSIs) - Fasdi Nik Ismail, Nik; Johari, Dalina; Aminuddin, Norzaina; Hashim, Norazlan (International Journal of Engineering and Technology, 2019)
In this paper a comparative study between two types of switching PWM signals namely Phase Disposition PWM (PDPWM) and Phase Opposition Disposition PWM (PODPWM) for three types of Multilevel Voltage Source Inverter (MVSI) are conducted. The selected MVSI topologies are cascaded H-bridge, flying capacitor and neutral point clamped MVSI. In general, the THD of the output voltage and current can be improved as the levels of MVSI inverters are increased. However, as the levels of outputs are increased the numbers of circuit components are also increased.  As a result, this will increase the circuit complexity for the MVSI to be operated at high levels.  From the study, it can be found that cascaded H-bridge inverter required the lowest number of circuit components and has better THD compared to the other two topologies of MVSI for the similar output voltage and current levels. Moreover, the proper selection of PWM control strategy technique between PDPWM and PODPWM for MVSI is also able to reduce the THD in the output waveform.  The circuit simulations for the MVSIs are simulated with MATLAB/SIMULINK simulation software.